2003
DOI: 10.1207/s15326985ep3801_4
|View full text |Cite
|
Sign up to set email alerts
|

The Expertise Reversal Effect

Abstract: When new information is presented to learners, it must be processed in a severely limited working memory. Learning reduces working memory limitations by enabling the use of schemas, stored in long-term memory, to process information more efficiently. Several instructional techniques have been designed to facilitate schema construction and automation by reducing working memory load. Recently, however, strong evidence has emerged that the effectiveness of these techniques depends very much on levels of learner e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
611
2
49

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,370 publications
(696 citation statements)
references
References 108 publications
34
611
2
49
Order By: Relevance
“…However, as the prior knowledge test has indicated the learners in this experiment already possessed some knowledge in the domain. There is accumulating evidence that the effectiveness of instructional guidelines depends on the level of domain knowledge of learners (Kalyuga 2005;Kalyuga et al 2003;Reisslein et al 2006). In fact, guidelines that are effective for novices in a domain may prove to be ineffective or even detrimental when applied to more proficient learners.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the prior knowledge test has indicated the learners in this experiment already possessed some knowledge in the domain. There is accumulating evidence that the effectiveness of instructional guidelines depends on the level of domain knowledge of learners (Kalyuga 2005;Kalyuga et al 2003;Reisslein et al 2006). In fact, guidelines that are effective for novices in a domain may prove to be ineffective or even detrimental when applied to more proficient learners.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, would male and female students differ in the degree to which learning and transfer (Question 2a) and self-efficacy 1 Note that for students who have some prior knowledge of solving probability calculation problems, examples would lose their effectiveness or may even start to hamper learning compared to practice problem solving (Kalyuga et al 2001; this is an example of the expertise-reversal effect; see Kalyuga et al 2003;Kalyuga and Renkl 2010). and perceived competence (Question 2d) would be enhanced, mental effort invested in the test reduced (Question 2c), and in the degree that students invest mental effort during example study (Question 2b), depending on whether they observed a video modeling example that presented a male or a female model? Based on the model-observer similarity hypothesis, we could expect novice learners to identify more with a same-gender model relative to an opposite-gender one and therefore show cognitive and affective benefits when learning from a same-gender model (Schunk 1987).…”
Section: The Present Studymentioning
confidence: 99%
“…According to the cognitive load theory, directing novices' attention to essential parts of animations compensates for a lack of cognitive schemata and frees up cognitive resources for relevant learning activities. However, once learners are capable of discerning relevant from irrelevant parts of animations, visual cues may provide redundant information that cannot be ignored, and hence may cause unnecessary cognitive load that hinders learning (within cognitive load theory referred to as the expertise reversal effect, Kalyuga et al 2003).…”
Section: Guiding Attention To Essential Informationmentioning
confidence: 99%